Niveles séricos de zinc, andrógenos, leptina, lípidos y lipoproteínas en pacientes con diabetes mellitus tipo 2: efectos del tratamiento con sulfato de zinc - Partida Hernández, Guadalupe (Universidad Autónoma Metropolitana, 2007)
The type-2 Diabetes mellitus patients display a marked reduction in their life expectancy ranging from 5 to 10 years, as well as a strong tendency towards developing microvascular (neuropathy), macrovascular (myocardial infarction) complications and erectile dysfunction; that induces a reduction of the quality of life of these subjects and an increase of the employement of the services provided by health institutions. Abnormal plasma levels of either trace elements such as chrome and zinc, lipid hormonal profile are known are frequently found in uncontrolled-diabetic patients. However, lipid alterations are a major determinant for the emerging macrovascular complications leading to death of these patients. Zinc-sulfate (ZnSO4 ) supplementation may be the therapeutical resource for recovering the trace element concentrations and modifying DM2 patients' metabolic and hormonal profiles. The aim of this study was to analyze metabolic and hormonal profile of DM2 patients treated with glibenclamida, with zinc levels lower than Mexican reference average and who were treated with 100 mg/day of ZnSO4 in a double-blind, cross-over, placebo-controlled (starch) pharmacological design. Both ZnSO4 and cornstarch as placebo were orally administered. The sample was made up of 30 male volunteers aged from 35 to 65 years old, with a DM2- established diagnosis with an evolution of 5 to 10 years, with no toxicomanies, treated with glibenclamida in an outpatient program. All the patients signed their written informed consent. The following biochemical parameters were quantified in blood samples: zinc serum concentration, glycosylated hemoglobin, fasting glycemia, lipid and liprotein profile, luteinizing hormone, follicle-stimulating hormone, prolactin, sex hormone-binding globulin, leptin, insulin, androstenedione, free testosterone, total testosterone and dihydrotestosterone. Intra- and interanalysis variate coefficients were lower than 5%. For data processing, a computerized statistical analysis system SPSS, version 10, was employed and the statistical significance was taken into account when p value was lower than 0.05 The results showed the beneficial effects achieved by DM2 patients with a low initial zinc concentration after a 12-week ZnSO4 treatment. Serum normalization of the above mentioned oligoelement, as well as changes in their lipid profile owing to decreased triglycerides, total cholesterol and c-VLDL lipoproteins levels. Concentrations of prolactin and insulin also were reduced. Increases of the levels of c-HDL, leptin, androstenedione, total testosterone, free testosterone and dihydrotestosterone were observed, with statistically significant difference as compared with starch treatment. The treatment with 100 mg ZnSO4 daily was well tolerated, the glycosylated hemoglobin, venous glucose, c-LDL, LH, FSH and sex hormone-binding globulin levels were not statistically significant. The daily administration of 100 mg of ZnSO4 to patientes with DM2 could reduce the incedence of cardiovascular or erectile dysfunction. More studies are needed in order to establish it. Key words: Type-2 Diabetes mellitus / zinc supplementation / zinc sulfate therapeutical effects / lipid and hormonal profile.; Los pacientes con Diabetes mellitus tipo 2 muestran una marcada reducción en su expectativa de vida de entre 5 y 10 años, así como una fuerte tendencia hacia el desarrollo de complicaciones microvasculares (neuropatía), complicaciones macrovasculares (infarto de miocardio), disfunción eréctil, lo que ocasiona una reducción de la calidad de vida de estos individuos, con una gran presión para sus familiares y un incremento en la necesidad de recurrir a los servicios proporcionados por Instituciones de salud. En personas con diabetes descontrolada es más frecuente encontrar niveles plasmáticos anormales de elementos traza como el cromo y el zinc, del perfil lipídico, del perfil hormonal. Las alteraciones en los lípidos son determinantes de la aparición de complicaciones macrovasculares que producen la muerte de esos pacientes. La suplementación con sulfato de zinc (ZnSO4 ) puede ser el recurso terapéutico para recuperar las concentraciones del elemento traza y modificar los perfiles metabólico y hormonal de pacientes con DM2. El propósito de este trabajo fue analizar el perfil metabólico y hormonal de pacientes con DM2, con niveles de zinc menores al promedio de referencia en mexicanos, tratados con glibenclamida a quienes se les administraron 100 mg/día de ZnSO4 , bajo un diseño farmacológico doble ciego, cruzado, en ensayo clínico controlado con almidón como placebo, ambos administrados por vía oral. La muestra estuvo constituida por 30 varones voluntarios, de 35 a 65 años de edad, con diagnóstico establecido de DM2 con una evolución de 5 a 10 años, sin toxicomanías, tratados con glibenclamida. Todos los pacientes firmaron carta de consentimiento informado. En muestras sanguíneas venosas se determinaron los siguientes parámetros bioquímicos: concentración sérica de zinc, hemoglobina glucosilada, glucemia de ayuno, perfil de lípidos y lipoproteínas, hormona luteinizante, hormona estimulante del folículo, prolactina, globulina unidora de hormona sexual, leptina, insulina, androstenediona, testosterona libre, testosterona total y dihidrotestosterona. Los coeficientes de variación intra e interanálisis fueron menores del 5 %. Para procesar los datos se utilizó el sistema computacional de análisis estadístico SPSS, versión 10 y la significancia estadística se consideró cuando el valor de p < 0.05 Los resultados mostraron los efectos benéficos del tratamiento con el ZnSO4 durante doce semanas en los pacientes con DM2 y con concentración inicial baja en zinc. La normalización sérica del oligoelemento se asoció con cambios en su perfil lipídico, disminuyendo los niveles de triglicéridos, colesterol total y de las lipoproteínas c-VLDL. Las concentraciones de prolactina y de insulina también disminuyeron. Se observaron incrementos en las concentraciones de c-HDL, leptina, androstenediona, testosterona total, testosterona libre y dihidrotestosterona, con diferencia estadísticamente significativa en comparación con el tratamiento de almidón. El tratamiento con 100 mg/ día de ZnSO4 fue bien tolerado y no hubo cambios signifcativos en los niveles de hemoglobina glucosilada, glucosa venosa, lipoproteína c-LDL, LH, FSH y globulina unidora de hormona sexual. La administración de 100 mg/ día de ZnSO4 a pacientes con DM2 podría reducir la incidencia de complicaciones cardiovasculares o de disfunción eréctil, pero se requieren más estudios para poderlo afirmar. Palabras clave: Diabetes mellitus tipo 2 / suplementación con zinc / efectos terapéuticos del sulfato de zinc / perfil de lípidos y de hormonas,